Disability in the Christian tradition : a reader - Brock, Brian, 1970-; Swinton, John, 1957- (W.B. Eerdmans Pub. Co., 2012)
This book brings together for the first time the views of renowned Christian leaders throughout history - including Augustine, Aquinas, Julian of Norwich, Luther, Calvin, Hegel, Kierkegaard, van den Bergh, Bonhoeffer, Barth, Vanier, and Hauerwas. Fourteen experts in theology and disability studies guide readers through each era or group of thinkers, offering clear commentary and highlighting important themes. --from publisher description.